Development of an Optimized Keyboard for the Tamazight Language: Integration of the Letter Frequency Model for Improved Ergonomics and Efficiency - Abderrahmane Badis, (International Journal of Computer (IJC), 2024)
The need for an ergonomic keyboard layout to minimize strain on wrists and fingers during prolonged use has become increasingly important with the proliferation of digital devices. For languages without a standardized keyboard layout, such as Tamazight, makeshift solutions have been used, leading to discomfort and strain on the user's hands and wrists, occasionally resulting in conditions such as repetitive strain injury (RSI) and tendonitis in the wrists. This study presents a novel approach to developing an optimized keyboard layout for Tamazight that focuses on user comfort and minimizes strain on the wrists and fingers. A keyboard stress model was developed in which the keys are classified according to their degree of difficulty and stress, taking into account the position of the keys and the strength and length of the fingers. A textual analysis of novels and songs with over 17,000 words in Tamazight was conducted to determine for the first time the frequency-letter model for the Tamazight language, mainly Kabyle. The frequency of use of each letter was used to distribute them based on the estimated stress level for each finger on the keyboard. The resulting layout minimizes the need for frequent finger switching and includes all the necessary additional keys for Tamazight language use, which is a significant improvement and a major step forward for the standardization of the Tamazight keyboard. The finished layout was implemented with the Microsoft Keyboard Layout Creator (MSKLC).